2014
DOI: 10.1155/2014/570546
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Care for HIV-Infected Patients with Co-Occurring Substance Use Disorder or Psychiatric Disease: Report from a Large, Integrated Health Plan

Abstract: Background. The costs of providing care to HIV-infected (HIV+) patients with co-occurring diagnoses of substance use (SU) disorder or psychiatric disease (PD) are not well documented. It is our objective to evaluate costs in these HIV+ patients receiving care in a large health plan. Methods. We conducted a retrospective cohort study from 1995 to 2010 to compare costs of healthcare in HIV+ patients with and without co-occurring SU disorder and/or PD diagnoses. Estimates of proportional differences in costs (rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…It is important to assess HIV infected persons for physical problems because of the high level of depression among HIV-infected persons and because the use of substances may impact the patient’s adherence to antiretroviral treatment (Skalski et al 2015 ). Studies have shown that there is an increase in mental disorders associated with substance use and among patients infected with HIV (Chander, Himelhoch & Moore 2006 ; DeLorenze et al 2014 ; Skalski et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to assess HIV infected persons for physical problems because of the high level of depression among HIV-infected persons and because the use of substances may impact the patient’s adherence to antiretroviral treatment (Skalski et al 2015 ). Studies have shown that there is an increase in mental disorders associated with substance use and among patients infected with HIV (Chander, Himelhoch & Moore 2006 ; DeLorenze et al 2014 ; Skalski et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the majority (80%) of the participants believe that it is of great importance to implement a national policy framework that integrates mental healthcare services into HIV services. The integration of these services into one clinic will help to reduce costs and increase the efficiency in the management of patients that present with these conditions (DeLorenze et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next to a negative influence of depressive symptoms on the quality of life of PLWH (2,3), the symptoms are also associated with high healthcare costs (4)(5)(6). These healthcare costs, such as inpatient and outpatient services and use of medication, for PLWH with depression (or other psychiatric diseases) varied a lot between studies, from $17,911 to $33,037 per person per year in the USA between 1995 and 2010 (4)(5)(6). In addition to direct healthcare costs, more indirect costs related to losses in productivity from work due to illness may be present.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, older PWLH have high rates of multimorbidity (Sangarlangkarn & Appelabaum, 2016;Kim & Ritchie, 2016). Chronic pain and substance use occur commonly in this population and are associated with poor health outcomes (Jiao et al, 2016;Parsons, Starks, Millar, Boonrai, & Marcotte, 2014;Edelman, Tetrault, & Fiellin, 2014) and increased use of healthcare services (Jiao et al, 2016;DeLorenze, Tsai, Horberg, & Quesenberry, 2014). PLWH are also at risk for declining physical functioning and reduced physical performance (Brooks, Buchacz, Gebo, & Mermin, 2012;Greene et al, 2014).…”
Section: Introductionmentioning
confidence: 99%